O przyjemności (voluptas) w twórczości Kwintusa Horacjusza Flakkusa - Pacewicz, Artur (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
In the poetry of Horace, one can find two statements in the first person singular that point to the possible philosophical position of their lyric subject. The first one identifies this position with Cyrenaism (Ep. I 1) and the other one – with Epicureanism (Ep. I 4). While both philosophies are concerned with the concept of pleasure, which is elevated here to the highest value, they understand it differently. This paper is divided into two parts. The former offers a short reconstruction of the concept of pleasure in the aforementioned philosophies and the latter presents an analysis of those fragments of Horace’s poetry in which the concept of voluptas appears. The analysis shows that in his poetry Horace is inclined to Epicurean rather than to Cyrenaic philosophy.
Keywords: Horace; Aristippus of Cyrene; Augustan poetry; philosophy; Cyreneans; voluptas